O emprego de okara no processamento de hambúrger de frango fermentado com Lactobacillus acidophilus CRL 1014 - Bomdespacho, Laura de Queiroz [UNESP]; Cavallini, Daniela Cardoso Umbelino [UNESP]; Castro, Ana Dóris de [UNESP]; Rossi, Elizeu Antônio [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Okara is a residue of production process of soy milk, wich has a considered nutritional value for containing proteins, lipids and fi bers in signifi cant amount, besides bioactive compounds, such as isofl avone. Despite these qualities, the great amount of okara produced annually in Brazil and in other countries generates a problem of disposal waste and it has served only for animal food products. Such situation can be changed by studies, that demonstrate the viability of okara’s utilization in human nourishment. Thus, the purpose of this research was to develop a fermented hamburger with a probiotic bacteria, based on chicken meat and okara fl our. Five formulations were processed: F1-100% of chicken meat, unfermented and containing curing salts, F2-100% of chicken meat, fermented with L. acidophilus, F3 - 90% of chicken meat and 10% of okara meal, fermented with L. acidophilus, F4 - 70% of chicken meat and 30% of okara meal, fermented with L. acidophilus; F5 - 50% of chicken meat and 50% of okara meal, fermented with L. acidophilus. All formulations were evaluated for the viability of the probiotic culture, determination of cooking yield and shrinkage percentage, pH and sensory characteristics. The results have demonstrated that it is possible to elaborate a chicken hamburger, fermented with Lactobacillus acidophilus CRL 1014, with the addition of 10% okara fl our.

Okara é o resíduo do processo de produção de leite de soja de valor nutricional considerável por apresentar proteínas, lipídeos e fi bras em quantidades signifi - cativas, além de compostos bioativos como as isofl avonas. Grandes quantidades de okara produzidas anualmente no Brasil e demais países têm servido apenas para a alimenta- ção de animais. Tal situação pode ser modifi cada por meio de estudos que demonstrem a viabilidade de sua utilização na alimentação humana. Nesse sentido, a proposta deste trabalho foi desenvolver um “hambúrguer” fermentado com cultivo probiótico à base de carne de frango e com adição de farinha de okara. Foram processadas cinco formulações: F1- 100% de carne de frango não fermentada e contendo sais de cura; F2- 100% de carne de frango fermentada com L. acidophilus; F3 - 90% de carne de frango e 10% okara fermentada com L.acidophilus; F4 - 70% de carne de frango e 30% okara fermentada com L.acidophilus; e F5 - 50% de carne de frango e 50% okara fermentada com L.acidophilus. Todas as formulações foram avaliadas quanto à viabilidade do cultivo probiótico, determinação de rendimento na cocção e porcentagem de encolhimento, pH e características sensoriais. Os resultados indicaram que é viável a elaboração de um produto do tipo “hambúrguer”, fermentado com Lactobacillus acidophilus CRL 1014, à base de carne de frango, adicionado de 10% de farinha de okara.
The use of soy residue (Okara) in the processing of chicken hamburger, fermented with Lactobacillus acidophilus CRL 1014
Keywords: Chicken meat; Hamburger; Okara; Probiotics; Curing salts; Carne de frango; Hambúrguer; Okara; Probióticos; Sais de cura